Making Climate Change History : Documents from Global Warming's Past - Howe, Joshua P. (Book collections on Project MUSE., 2017)
"Making Climate Change History is a short, user-friendly collection of primary sources selected from the most important--and often the most overlooked--documents in the scientific and political history of anthropogenic climate change. It provides students, teachers, researchers and interested readers with the raw materials with which to construct a narrative of climate change in the twentieth century. It also provides a framework for developing historians to learn to work with a diverse array of primary sources, including scientific articles. This reader also makes its own case for how the stakes of conversations about climate change have become increasingly clear over time in terms of causes and consequences, and argues for the relevance of history to building just, equitable and effective strategies for dealing with the climatic challenges of the future"--Provided by publisher.